Uji Aktivitas Antioksidan Ekstrak Kasar Keong Bakau (Telescopium telescopium) dengan Pelarut yang Berbeda terhadap Metode DPPH (Diphenyl Picril Hidrazil) - Rahmayani, Ulfah; Pringgenies, Delianis; Djunaedi, Ali (977-2407769)
Mangrove snail (Telescopium telescopium) is one of the marine gastropod and some communities use as foodstuff. The purpose of study was to find out the antioxidant activity by crude extract of mangrove snails (T. telescopium) using DPPH method in different solvents. The method consists of extraction using gradient solvent (chloroform, ethyl acetate and methanol), phytochemical test and antioxidant activity test using DPPH method. DPPH test using a series of concentration of 100 ppm, 200 ppm, 400 ppm and 800 ppm with triplicate repetition. IC50 values were determined by calculating the regression analysis % inhibition against the concentration of crude extract. The crude extract of mangrove snails is contained three bioactive components in the form of alkaloids, steroids and flavonoids.The results showed that the IC50 value of chloroform, ethyl acetate and methanol extract were 47274.00 ppm, 4143.58 ppm and 2329.81 ppm, respectively. The IC50 values of all crude extract have a very weak antioxidant activity (IC50 > 200 ppm), with IC50 of BHT as positive control was 4.91 ppm.